Sylvia Plath: A Hungarian Bibliography - Vadon, Lehel (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The present bibliography makes available for the first time a resonably complete record of her publications—both primary and secondary sources—in Hungary. The books in Primary Sources are listed in chronological arrangement published in Hungary. Plath’s other works in Hungarian translation or in the original are arranged in order of publication date in Hungary. Secondary Source items are presented under the names of the authors, listed in alphabetical order. Entries by unknown authors are arranged in chronological order.